A new intertidal barnacle, Chthamalus ngankeeae sp. nov. (Balanomorpha: Chthamalidae) from the Malaysian Peninsula and western Borneo waters - Chan, Benny K. K.; Tsai, Pei-Chen; Tsao, Yao-Feng (Zootaxa, 2024)
The present study identified a new barnacle species from Malaysian waters, Chthamalus ngankeeae sp. nov., on morphological and molecular grounds. Chthamalus ngankeeae sp. nov. is an intertidal species that is abundant on high shores, above the oyster zone. Chthamalus ngankeeae sp. nov. has two morphotypes, based on shell colour. Brown morphs have brown shells with pale brown ridges and look similar to Microeuraphia withersi (Pilsbry, 1916). Chthamalus ngankeeae sp. nov. has four teeth on the mandible, while M. withersi has but three. White morphs of C. ngankeeae sp. nov. possess white shells with gray ridges. The white morph of C. ngankeeae sp. nov. is similar to C. moro Pilsbry, 1916, but a major morphological difference includes a more prominent articular ridge on the scutum of C. ngankeeae sp. nov. compared to C. moro. Molecular analyses of sequence divergence in the COI and NaK genes of C. ngankeeae sp. nov. with other chthamalids showed that it forms an individual monophyletic group and does not belong to any of the cryptic lineages of C. moro, supporting its designation as a new species.